1020 Association of Sleep Duration with Cognitive Function in U.S. Older Adults. (27th April 2018) - Low, D; Wu, M; Spira, A
Abstract: Introduction: Excessive and insufficient sleep have been associated with cognitive dysfunction. The sleep duration recommended for adults aged 65+ by the National Sleep Foundation is 7–8 hours, with 5, 6, or 9 hours considered potentially appropriate. We investigated the association between sleep duration and cognitive performance in adults aged 65+. Methods: Participants were 901 adults aged 65+ from the National Health and Nutrition Examination Survey 2011–12 dataset, who had data on self-reported sleep duration, covariates, and tests of cognitive function: Consortium to Establish a Registry for Alzheimer's Disease Word Learning (CERAD-WL immediate and delayed), Animal Fluency Test (AFT), and Digital Symbol Substitution Test (DSST). Sleep duration (hours) was categorized as: ≤4, 5–6, 7–8 (reference), 9, and ≥10. We excluded outliers of 2 or ≥12 hours. Regression analyses were performed with sample weights applied to obtain nationally representative results. Results: The mean±SD age of the participants was 72.7 ± 0.2; 44.3% were men; 80.8% were non-Hispanic White; 57.1% received some college education; 3.3% slept for ≤4 hours, 24.2% for 5–6 hours, 61.7% for 7–8 hours, 7.9% for 9 hours, and 3.0% for ≥10 hours. In unadjusted analyses, compared to participants with 7–9 hours of sleep, those with ≥10 had poorer immediate CERAD-WL[β(95%CI) -3.57(-6.04, -1.10)] and DSST[β(95%CI) -11.11(-18.78, -3.44)]; those with ≤4 or ≥10 hours had poorer AFT[β(95%CI) -2.44(-4.16, -0.73)] and [β(95%CI) -4.23(-5.36, -3.10)], respectively; those with 5–6 hours had better delayed CERAD-WL[β(95%CI) 0.63(0.16, 1.11)]; those with 9 or ≥10 hours had poorer delayed CERAD-WL[β(95%CI) -0.91(-1.71, -0.10)] and [β(95%CI) -1.44(-2.76, -0.11)], respectively. After adjusting for age, race/ethnicity, gender, and education, compared to participants with 7–9 hours of sleep, those with ≥10 hours had poorer immediate CERAD-WL[β(95%CI) -2.35(-4.47, -0.23)] and AFT[β(95%CI) -2.31(-3.71, -0.91)] performance; those with 5–6 hours had better delayed CERAD[β(95%CI) 0.61(0.20, 1.02)]. There was no significant association with DSST. Conclusion: In adults aged 65+, prolonged sleep duration is associated with poorer immediate verbal learning and semantic fluency performance. Shorter sleep duration is associated with better delayed verbal learning. Further prospective studies with objective sleep measures in representative cohorts are needed. Support (If Any): NIA R01AG050507, RF1AG050745, R01AG049872, U01AG052445, R01AG054771. NHANES 2011–12 https://wwwn.cdc.gov/nchs/nhanes/Search/DataPage.aspx?Component=Questionnaire&CycleBeginYear=2011 .